Role Of Higher Education In Developing Women Empowerment And Removal Gender Inequality. - Anindita Borgohain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Higher Education provides to women that means independence in decision making. It would develop the capabilities and responsibities in the field of social, economic, political and cultural areas. Higher Education means whole development of personality. Higher education insured that you will have a better job that will provide stability in life. It means self improvement, job insurance, a development of character and social improvement. India holds the second position in the world of having highest population. There are approximately 49% female in total population of it. But if we analyse the current status of Indian women with other countries of the world than we can realise that the scene is not even satisfactory. Indian women generally faced all types of barriers to success like illiteracy, domestic violence, lack of motivation and support and many more. India is a country where man domains in the society prevail. It is essential for the harmonious development of the country that women should go hand by hand and shoulder to shoulder with men. And for empowering the women, Higher Education will play vital role. The paper describes the facts related to women empowerment. It widely discusses gender related issues in terms of education, health, their share in employment and national parliament.